2009 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--5584
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating The Effectiveness And Use Of Cyber Learning Environments In Engineering Education: A Qualitative Analysis

Abstract: with a joint appointment in the Department of Engineering and Science Education and the School of Computing. Before his appointment at Clemson, he served as a Research Scientist in the Science Gateways Group at the Rosen Center for Advanced Computing, Information Technology at Purdue University where he led the education and the educational technology effort for the NSF-funded Network for Computational Nanotechnology (NCN). Dr. Madhavan was the Chair of the IEEE/ACM Supercomputing Education Program 2006 and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A systematic survey of Journal of Engineering Education articles published from 1999 to 2008 found only three articles that dealt with student collaboration and communication over the Internet. 37 One study compared performance and satisfaction of face-to-face and virtual teams in a random control experiment in a graduate course on lean manufacturing. 70 The investigators reported similar performance on the project and in the group process patterns, but the face-toface teams were more satisfied with the experience.…”
Section: Effectiveness Of Virtual Approachesmentioning
confidence: 99%
“…A systematic survey of Journal of Engineering Education articles published from 1999 to 2008 found only three articles that dealt with student collaboration and communication over the Internet. 37 One study compared performance and satisfaction of face-to-face and virtual teams in a random control experiment in a graduate course on lean manufacturing. 70 The investigators reported similar performance on the project and in the group process patterns, but the face-toface teams were more satisfied with the experience.…”
Section: Effectiveness Of Virtual Approachesmentioning
confidence: 99%
“…Instead of studying engineering education as a whole, some projects focused on a particular research topic. Madhavan et al 13 provided a synthesis of cyberlearning environments based on a qualitative analysis of articles in the Journal of Engineering Education between 2000 and 2009. Similarly, Prince 14 studied the effectiveness of active learning by synthesizing relevant literature, whereas Dutson et al investigated the topic of teaching engineering design 15 .…”
Section: Current Approaches To Characterizing a Research Domain Using Data And Visualizationmentioning
confidence: 99%
“…27 A systematic survey of Journal of Engineering Education articles published from 1999 to 2008 found only three articles that dealt with student collaboration and communication over the Internet. 17 One compared performance and satisfaction of face-to-face and virtual teams in a random control experiment in a graduate course on lean manufacturing. 26 The investigators reported similar performance on the project and in the group process patterns but the face-to-face teams were more satisfied with the experience.…”
Section: Virtual Approaches To Faculty Developmentmentioning
confidence: 99%